Characterization and identification of a plastic-like off-odour in mineral water. - Strube, Andrea; Büttner, Andrea; Groetzinger, Carola (Water Science and Technology: Water Supply, 2009)
A specific mineral water off-odor, the so-called "sunlight" flavor produced after UV light exposure, was characterized by sensory analysis in different mineral water samples and ranked according to overall odor intensity. The odorants were isolated by means of solvent extraction and stir bar sorptive extraction (SBSE) techniques, respectively. Analyses were performed with two-dimensional (2D) high resolution gas chromatographic (HRGC) separation and parallel mass spectrometric (MS) and olfactometric (O) detection. Additionally, analyses of off-odor-free samples exposed to natural sunlight or to "artificial" UV radiation (replicating natural sunlight) were analyzed to assess off-odor compound formation. 14 common characteristic odorants in commercial off-odor and irradiated samples were identified. These were predominantly saturated and mono or di-unsaturated carbonyl compounds, with several substances exhibiting the characteristic fatty and plastic-like odor impressions. Eight of the compounds identified were detected for the first time as off-odor "sunlight" flavor contributors to mineral water and had amongst the highest flavor dilution (FD) factors in the extracted samples.<br